Sciatic nerve regeneration in KLF7-transfected acellular nerve allografts. (3rd March 2016) - Wang, Ying; Li, Wen-Yuan; Sun, Ping; Jin, Zai-shun; Liu, Gui-bo; Deng, Ling-Xiao; Guan, Li-Xin
Abstract : Objective : Krüppel-like Factor 7 (KLF7) is a transcription factor that promotes axon regeneration in the central nervous system. Here, we assessed whether KLF7 stimulates regeneration after peripheral nerve injury. Methods : C57BL/6 mice received an acellular nerve allograft (ANA) injected with either adeno-associated virus 2 (AAV2) vector or AAV2-KLF7 for sciatic nerve gap repair. After 4 weeks, KLF7 was detected by RT-PCR, western blot and immunohistochemistry in regenerated nerves. Axonal regeneration and functional recovery were examined by immunohistochemistry, Fluorogold (FG) and cholera toxin B (CTB) retrograde neural tracing, sciatic function index (SFI), angle of ankle, Hargreaves test and electrophysiological analysis. Results : With AAV2-KLF7 injection, KLF7 expression increased in regenerated nerves, and amplitude, score of SFI, angle of ankle and FG-labelled spinal cord neurons were increased. We observed elevated CTB-labelled neurons in dorsal root ganglia (DRG), neurofilaments, P0 (peripheral myelin) and S100 and decreased latency period and withdrawal latencies in the Hargreaves test. The SFI was significantly correlated with amplitude and regenerated axon number. Tyrosine kinase A (TrkA) and B (TrkB) receptors were also increased in the DRG. Conclusions : Our findings suggest that KLF7 promoted peripheral nerve axonal regeneration, further supporting a role for KLF7 as a growth-promoting transcription factor in the injured nervous system.